The Development of Android-Based Digital Pocketbook Learning Media on Short Story Materials - Idham Syafri Marliansya; Ratu Wardarita; Muhammad Ali; Gunawan Ismail (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2023)
The aims of this study were: a) to describe the needs of students and teachers for android-based digital pocketbook learning media at SMK Negeri 1 Palembang; b) to describe the results of the design of android-based digital pocketbook learning media at SMK Negeri 1 Palembang; and c) to describe the validation results of android-based digital pocketbook learning media at SMK Negeri 1 Palembang. In the method used in this development, researchers refer to the research and development (R&D) model using the